SYARIAT SIMBOLIK DAN ISLAMISASI NEGARA: EKSPERIMENTASI PERDA SYARI’AT SEBAGAI JALAN BARU MENUJU NEGARA ISLAM - Kholiludin, Tedi (Universitas Wahid Hasyim Semarang, 2020)
Abstract This paper discusses one of the phenomena that erupted Post-Reformation is a desire to make rules in areas removed from the spirit of Islamic law. Appearing later legislation on dressmaking, ask for compensation as well curfew for women. Understanding Islamic Sharia in the context of a plural society like Indonesia is a research question asked in this paper. In conclusion, the substance of the Shari'a must first be made as reference material from the formalist Shari'a.